Examining How Proactive Management and Culturally Responsive Teaching Relate to Student Behavior: Implications for Measurement and Practice. Issue 2 (1st June 2018) - Larson, Kristine E.; Pas, Elise T.; Bradshaw, Catherine P.; Rosenberg, Michael S.; Day-Vines, Norma L.
Abstract: The discipline gap between White students and African American students has increased demand for teacher training in culturally responsive and behavior management practices. Extant research, however, is inconclusive about how culturally responsive teaching practices relate to student behavior or how to assess using such practices in the classroom. Identifying proactive behavior management and culturally responsive teaching practices that are associated with positive student behavior may inform teacher training and bolster efforts to reduce disparities in behavioral and academic performance. The current study examined the association between student behaviors and the observed use of and teacher self-reported efficacy in using culturally responsive teaching and proactive behavior management practices. Data were collected from 274 teachers in 18 schools. Structural equation modeling indicated a statistically significant association between observations of culturally responsive teaching and proactive behavior management practices, with observed positive student behaviors in classrooms. Implications for measurement and practice are discussed.